Cotton polyamine oxidase is required for spermine and camalexin signalling in the defence response to Verticillium dahliae - Huijuan Mo; Xingfen Wang; Yan Zhang; Guiyin Zhang; Jinfa Zhang; Zhiying Ma (2015)
Verticillium dahliae is a destructive, soil-borne fungal pathogen that causes vascular wilt disease in many economically important crops worldwide. A polyamine oxidase (PAO) gene was identified and cloned by screening suppression subtractive hybridisation and cDNA libraries of cotton genotypes tolerant to Verticillium wilt and was induced early and strongly by inoculation with V. dahliae and application of plant hormone. Recombinant cotton polyamine oxidase (GhPAO) was found to catalyse the conversion of spermine (Spm) to spermidine (Spd) in vitro. Constitutive expression of GhPAO in Arabidopsis thaliana produced improved resistance to V. dahliae and maintained putrescine, Spd and Spm at high levels. Hydrogen peroxide (H2 O2 ), salicylic acid and camalexin (a phytoalexin) levels were distinctly increased in GhPAO-overexpressing Arabidopsis plants during V. dahliae infection when compared with wild-type plants, and Spm and camalexin efficiently inhibited growth of V. dahliae in vitro. Spermine promoted the accumulation of camalexin by inducing the expression of mitogen-activated protein kinases and cytochrome P450 proteins in Arabidopsis and cotton plants. The three polyamines all showed higher accumulation in tolerant cotton cultivars than in susceptible cotton cultivars after inoculation with V. dahliae. GhPAO silencing in cotton significantly reduced the Spd level and increased the Spm level, leading to enhanced susceptibility to infection by V. dahliae, and the levels of H2 O2 and camalexin were distinctly lower in GhPAO-silenced cotton plants after V. dahliae infection. Together, these results suggest that GhPAO contributes to resistance of the plant against V. dahliae through the mediation of Spm and camalexin signalling.